Preparation method and application of an organically modified vermiculite-based catalyst for cellulose hydrolysis

The catalyst is prepared by organically modifying the vermiculite, which solves the problem that cellulose is difficult to hydrolyze under mild conditions, and achieves efficient cellulose hydrolysis and reducing sugar yields, and the catalyst is environmentally friendly and easy to recover.

CN116943726BActive Publication Date: 2025-06-10ZHEJIANG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310781477.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2025-06-10
Estimated Expiration
2043-06-29

AI Technical Summary

Technical Problem

Due to its chemically inert and polar properties, cellulose is difficult to hydrolyze under mild conditions, limiting its application in the field of renewable energy.

Method used

By organically modifying vermiculite, an organically modified vermiculite-based catalyst was prepared, and the catalyst was used in the cellulose hydrolysis reaction to promote the hydrolysis of cellulose using its high surface charge density and active sites.

Benefits of technology

The hydrolysis conversion rate of cellulose and the yield of reducing sugar are improved. The catalyst and product are easily separated, are non-corrosive, and are not polluted to the environment. The catalyst synthesis method is simple, easy to recover, and has a high reuse rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004310922840000011
    Figure HDA0004310922840000011
  • Figure HDA0004310922840000012
    Figure HDA0004310922840000012
  • Figure HDA0004310922840000021
    Figure HDA0004310922840000021
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of an organically modified vermiculite-based catalyst for cellulose hydrolysis. The preparation method comprises the following steps: preparing an aqueous solution of a surfactant, adding unmodified vermiculite or acid-modified vermiculite to the aqueous solution of the surfactant and stirring, ultrasonically dispersing it evenly, then placing the mixed solution in a sealed container, placing it in a constant temperature water bath and oscillating for reaction, after the reaction is completed, cooling it to room temperature, centrifuging the mixed solution after the reaction and washing it with water until the pH of the supernatant is 7-8, after the washing is completed, taking out the lower-layer solid, drying and grinding it to obtain the organically modified vermiculite-based catalyst. The present invention provides the application of the obtained organically modified vermiculite-based catalyst in the cellulose hydrolysis reaction, which has the advantages of high catalytic efficiency, small dosage, few by-products, etc., can improve the hydrolysis conversion rate of cellulose, and has a high reducing sugar yield; the catalyst is easy to separate from the product; it is non-corrosive and has no pollution to the environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a preparation method and application of an organically modified vermiculite-based catalyst for cellulose hydrolysis. Background Art

[0002] In recent years, due to the overexploitation of conventional fossil energy and the lack of new energy technologies, the energy available for human use has been decreasing day by day. At the same time, a series of problems such as environmental pollution and low energy utilization efficiency have emerged. Therefore, reducing energy consumption, researching and developing new renewable energy sources, improving energy utilization efficiency, and preventing environmental pollution have become problems that need to be jointly solved in the world today. As a renewable energy source, biomass has become a current research hotspot due to its advantages such as low cost, pollution-free, wide distribution, and recyclability. Lignocellulose is an important part of biomass resources and is the most abundant sustainable carbon source on the earth, with great development potential to replace other fossil fuels such as coal and oil. Cellulose is a substance formed by a series of linear glucose molecules into a flat ribbon structure and is a linear polymer. A large number of hydrogen bonds exist in cellulose molecules, resulting in its chemical inertness. At room temperature, cellulose is insoluble in water, including some aqueous solutions such as dilute alkali, and is also insoluble in organic solvents such as alcohol, ether, acetone, and benzene. Cellulose molecules are polar, and there are very strong intermolecular forces between different molecular chains. Therefore, cellulose is rigid and its properties are too stable to be depolymerized under mild conditions, which has led to its low utilization rate worldwide. For the application of cellulose biomass energy, cellulose is first hydrolyzed into reducing sugars such as glucose (TRS), and then some important platform chemicals including 5-HMF and furfural can be prepared, or a series of downstream products such as levulinic acid, ethylene glycol, and oxalic acid can be further prepared. In the past few decades, the conversion of cellulose into various value-added chemicals and fuels, such as various gluconic acids, lactic acids, alcohols, 5-hydroxymethylfurfural, 2,5-dimethylfuran, valeric esters, and levulinic acid, has also been developing rapidly and is widely used in the pharmaceutical, food, and industrial fields. Therefore, cellulose hydrolysis is crucial for realizing resource utilization.

[0003] Vermiculite is an inorganic silicate mineral, and its name comes from the Latin Vermicularis, meaning "worm-like". Vermiculite has many attractive features of clay minerals in its structure, including but not limited to active sites such as hydroxyl groups, Lewis and acidity, exchangeable interlayer cations, etc., and the presence of different Al in terms of chemical stability 2 (OH) 6 octahedral sheets and SiO 4Tetrahedral sheet (Madejová J. Ftir techniques in clay mineral studies[J]. Vibrational Spectroscopy, 2003, 31(1): 1-10.). Due to the structural characteristics of vermiculite, it exhibits different properties from other clay minerals in many fields.

[0004] In previous studies, it was found that layered clay minerals such as montmorillonite and kaolin showed good catalytic effects on cellulose hydrolysis after modification. In this invention, vermiculite is modified and applied to cellulose hydrolysis in order to obtain a higher TRS yield. Summary of the Invention

[0005] The technical problem solved by this invention is to provide a preparation method of an organically modified vermiculite-based catalyst for cellulose hydrolysis and its application in cellulose hydrolysis.

[0006] The following specifically describes the technical solutions adopted by this invention to achieve the above-mentioned invention purposes.

[0007] In the first aspect, this invention provides a preparation method of an organically modified vermiculite-based catalyst for cellulose hydrolysis, including the following steps:

[0008] Prepare an aqueous surfactant solution with a concentration of 5-20 g / L. The surfactant is selected from at least one of cetyltrimethylammonium bromide (CTAB), dodecyltrimethylammonium bromide (DTAB), sodium dodecyl sulfate (SDS), dimethyl sulfoxide (DMSO), and sodium dodecyl sulfonate (SLS). Add unmodified vermiculite or acid-modified vermiculite to the aqueous surfactant solution and stir, then ultrasonically disperse it evenly. Then place this mixed solution in a closed container, place it in a constant temperature water bath, and shake it at 50-80 °C for 3-8 h. After the reaction ends, cool it to room temperature. Centrifuge and wash the reaction mixture until the pH of the supernatant is 7-8. After the washing ends, take out the lower-layer solid, dry it, and grind it into 200-300 mesh to obtain the organically modified vermiculite-based catalyst.

[0009] Preferably, the acid-modified vermiculite is prepared by the following method:

[0010] Add unmodified vermiculite to an acid solution with a concentration of 5-40 wt%, ultrasonically disperse it evenly to obtain a mixed solution. Stir and react the obtained mixed solution at 60-100 °C for 3-8 hours. After the reaction ends, cool it to room temperature. Centrifuge and wash it until the pH of the supernatant is 6-7. Finally, dry it to obtain the acid-modified vermiculite.

[0011] As a further preference, the acid is sulfuric acid, phosphoric acid, nitric acid or hydrochloric acid. More preferably, the acid solution is a 15-35 wt% sulfuric acid solution or phosphoric acid solution, and even more preferably a 15-35 wt% sulfuric acid solution. Within this concentration range, increasing the acid concentration helps to improve the catalytic effect of the catalyst on cellulose hydrolysis.

[0012] As a preference, the surfactant is cetyltrimethylammonium bromide (CTAB) or dodecyltrimethylammonium bromide (DTAB), and most preferably cetyltrimethylammonium bromide (CTAB).

[0013] As a preference, the concentration of the surfactant aqueous solution is 20 g / L.

[0014] In a second aspect, the present invention provides the application of the organically modified vermiculite-based catalyst prepared according to the above method in the cellulose hydrolysis reaction.

[0015] The specific application is as follows: Add cellulose, the organically modified vermiculite-based catalyst and deionized water into a hydrothermal reaction kettle, seal it and heat it to 195-215 °C, and carry out the hydrolysis reaction for 2-5 hours to generate reducing sugar.

[0016] As a preference, the feeding ratio of the cellulose, the organically modified vermiculite-based catalyst and the deionized water is 1 g: 0.12-0.25 g: 10-25 mL.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0018] a) For the organically modified vermiculite-based catalyst provided by the present invention, the main source of the negative charge of the vermiculite group is the large amount of Al 3+ substituting Si 4+ , and the surface charge density is higher than that of clay minerals such as montmorillonite and kaolin, which helps to polarize and break the C—H bond in cellulose to generate reducing sugar.

[0019] b) Using the catalyst of the present invention for the cellulose hydrolysis reaction has the advantages of high catalytic efficiency, less dosage, less by-products, etc., can improve the cellulose hydrolysis conversion rate, and has a high reducing sugar yield; the catalyst and the product are easy to separate; it is non-corrosive and has no pollution to the environment.

[0020] c) The synthesis method of the organically modified vermiculite-based catalyst of the present invention is simple, easy to recycle, and the catalyst has a high reuse rate. Description of the Drawings

[0021] Figure 1 is the XRD pattern of different catalysts;

[0022] Figure 2 is the SEM image of different catalysts;

[0023] Figure 3 It is a result graph of the hydrolysis of cellulose catalyzed by vermiculite modified by intercalation of 20 g / L cationic surfactant cetyltrimethylammonium bromide (CTAB) and modified with different sulfuric acid concentrations.

[0024] Figure 4 It is a result graph of the hydrolysis of cellulose catalyzed by vermiculite modified by intercalation of 20 g / L CTAB and modified with different phosphoric acid concentrations.

[0025] Figure 5 It is a result graph of the production of TRS by the hydrolysis of cellulose catalyzed by different acid-modified vermiculites modified by 5 g / L and 10 g / L CTAB.

[0026] Figure 6 It is a result graph of the production of TRS by the hydrolysis of cellulose catalyzed by different acid-modified vermiculites intercalated with neutral surfactant dimethyl sulfoxide (DMSO) and cationic surfactant dodecyltrimethylammonium bromide (DTAB).

[0027] Figure 7 It is a result graph of the production of TRS by the hydrolysis of cellulose catalyzed by different acid-modified vermiculites intercalated with anionic surfactant sodium dodecyl sulfate (SDS) and sodium lauryl sulfonate (SLS). Specific Embodiments

[0028] The technical solutions of the present invention will be further described below with specific embodiments, but the protection scope of the present invention is not limited thereto:

[0029] In the embodiments of the present invention, those not specified under specific conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. For reagents or instruments not specified for the manufacturer, they are all conventional products that can be obtained by conventional technical means or purchased commercially.

[0030] Example 1

[0031] 1. Preparation of the catalyst

[0032] Take 20 mL of a 20 g / L cetyltrimethylammonium bromide (CTAB) solution and place it in a 100 mL beaker. Add 5 g of vermiculite (Vrm) to it and stir for 60 min. Then place it in an ultrasonic machine and ultrasonicate for 45 min to disperse it evenly. Then transfer the mixture to a 250 mL conical flask, seal the flask mouth, and place it in a constant temperature water bath at 70 °C and shake for 6 h. After the reaction is completed, cool it to room temperature. Centrifuge the reaction mixture at a centrifugation rate of 4500 r / min for 4 min, and wash it with deionized water multiple times until the pH of the supernatant is 7 - 8. After washing, take out the lower layer of solid and dry it in an oven at 80 °C. Grind the dried solid sample to 200 - 300 mesh to obtain the organically modified vermiculite catalyst 20-Vrm-16B. The XRD results of pure vermiculite (Vrm) are as shown in Figure 1 (a), and the SEM results are as shown in Figure 2 (1). The XRD results of the sample 20-Vrm-16B are as shown in Figure 1 (b), and the SEM results are as shown in Figure 2 (2).

[0033] 2. Cellulose hydrolysis

[0034] Weigh 0.5 g of cellulose (Shanghai Aladdin Biochemical Technology Co., Ltd.), 0.09 g of the 20-Vrm-16B catalyst, and 8 mL of deionized water (i.e., catalyst mass / cellulose mass = 0.18, deionized water mass / cellulose mass = 16), and mix them in a 25 mL stainless steel hydrothermal reaction kettle with a polytetrafluoroethylene lining. After sealing, heat the temperature to 205 °C and carry out the hydrolysis reaction for 3.5 h. After the reaction is completed, quickly cool the reaction kettle to room temperature, pour the reaction solution into a centrifuge tube, then centrifuge and filter. Take 0.5 mL of the supernatant and dilute it with distilled water. Take 1 mL of the diluted liquid, 1 mL of water, and 1.5 mL of DNS solution to measure the reducing sugar of the obtained hydrolysis product in a UV-visible spectrophotometer. The catalytic performance results are as shown in Figure 3 as follows.

[0035] Example 2

[0036] 1. Preparation of acid-modified vermiculite

[0037] Take 100 mL of 15 wt% sulfuric acid solution in a 250 mL beaker, add 5 g of vermiculite to it and stir. Place it in an ultrasonic machine and ultrasonicate for 30 min to make it disperse evenly. Then transfer the mixed solution to a three-necked round-bottom flask equipped with a condenser, a stirrer and a thermometer, stir at 70 °C for 6 h, and cool it to room temperature after the reaction ends. Centrifuge the reacted mixed solution several times at a centrifugation rate of 4500 r / min for 4 min. Wash it with deionized water several times until the pH of the supernatant is 6 - 7. After washing, take out the lower-layer solid and dry it in an oven at 80 °C. Grind the dried solid sample into 200 - 300 mesh, and name the sample Vrm-HS15. The XRD results of the sample are as Figure 1 (c) shows.

[0038] 2. Preparation of catalyst

[0039] Replace the vermiculite in step 1 of Example 1 with acid-modified vermiculite Vrm-HS15, and the others are the same as in Example 1. The obtained catalyst sample is named 20-Vrm-HS15-16B, and its XRD results are as Figure 1 (d) shows.

[0040] 3. Cellulose hydrolysis

[0041] The catalytic performance test method is as in step 2 of Example 1. The performance results are as Figure 3 shown.

[0042] Example 3

[0043] 1. Preparation of acid-modified vermiculite

[0044] Change the acid to 35 wt% sulfuric acid, and the other preparation steps are the same as in Example 2. The obtained sample is Vrm-HS35. The XRD results of the sample are as Figure 1 (e) shows, and the SEM results are as Figure 2 (3) shows.

[0045] 2. Preparation of catalyst

[0046] Replace the vermiculite in step 1 of Example 1 with acid-modified vermiculite Vrm-HS35, and the others are the same as in Example 1. The obtained catalyst sample is named 20-Vrm-HS35-16B, and its XRD results are as Figure 1 (f) shows, and the SEM results are as Figure 2 (4) shows.

[0047] 3. Cellulose hydrolysis

[0048] The catalytic performance test method is as in Example 1. The performance results are as Figure 3 shown.

[0049] Example 4

[0050] 1. Preparation of acid-modified vermiculite

[0051] The acid was changed to 5 wt% sulfuric acid, and other synthesis processes were the same as in Example 2. The obtained sample was named Vrm-HS5.

[0052] 2. Catalyst preparation

[0053] The vermiculite in Step 1 of Example 1 was replaced with acid-modified vermiculite Vrm-HS5, and the others were the same as in Example 1. The obtained catalyst sample was named 20-Vrm-HS5-16B.

[0054] 3. Cellulose hydrolysis

[0055] The catalytic performance test method was the same as in Example 1. The performance results are as Figure 3 shown.

[0056] Example 5

[0057] 1. Preparation of acid-modified vermiculite

[0058] The acid was changed to 10 wt% sulfuric acid, and other synthesis processes were the same as in Example 2. The obtained sample was Vrm-HS10.

[0059] 2. Catalyst preparation

[0060] The vermiculite in Step 1 of Example 1 was replaced with acid-modified vermiculite Vrm-HS10, and the other preparation processes were the same as in Example 1. The obtained catalyst sample was named 20-Vrm-HS10-16B.

[0061] 3. Cellulose hydrolysis

[0062] The catalytic performance test method was the same as in Example 1. The performance results are as Figure 3 shown.

[0063] Example 6

[0064] 1. Preparation of acid-modified vermiculite

[0065] The acid was changed to 20 wt% sulfuric acid, and other synthesis processes were the same as in Example 2. The obtained sample was Vrm-HS20.

[0066] 2. Catalyst preparation

[0067] The vermiculite in Step 1 of Example 1 was replaced with acid-modified vermiculite Vrm-HS20, and the other preparation processes were the same as in Example 1. The obtained catalyst sample was named 20-Vrm-HS20-16B.

[0068] 3. Cellulose hydrolysis

[0069] The catalytic performance test method was the same as in Example 1. The performance results are as Figure 3as shown

[0070] Example 7

[0071] 1. Preparation of acid-modified vermiculite

[0072] The acid was changed to 25 wt% sulfuric acid, and other synthesis processes were the same as in Example 2, and the obtained sample was Vrm-HS25.

[0073] 2. Catalyst preparation

[0074] The vermiculite in Step 1 of Example 1 was replaced with acid-modified vermiculite Vrm-HS25, and other preparation processes were the same as in Example 1, and the obtained sample was named 20-Vrm-HS25-16B.

[0075] 3. Cellulose hydrolysis

[0076] The catalytic performance test method was the same as in Example 1. The performance results are as Figure 3 as shown

[0077] Example 8

[0078] 1. Preparation of acid-modified vermiculite

[0079] The acid was changed to 30 wt% sulfuric acid, and other synthesis processes were the same as in Example 2, and the obtained sample was Vrm-HS30.

[0080] 2. Catalyst preparation

[0081] The vermiculite in Step 1 of Example 1 was replaced with acid-modified vermiculite Vrm-HS30, and other preparation processes were the same as in Example 1, and the obtained sample was named 20-Vrm-HS30-16B.

[0082] 3. Cellulose hydrolysis

[0083] The catalytic performance test method was the same as in Example 1. The performance results are as Figure 3 as shown

[0084] Example 9

[0085] 1. Preparation of acid-modified vermiculite

[0086] The acid was changed to 5 wt% phosphoric acid, and other synthesis processes were the same as in Example 2, and the obtained sample was Vrm-HP5.

[0087] 2. Catalyst preparation

[0088] The vermiculite in Step 1 of Example 1 was replaced with acid-modified vermiculite Vrm-HP5, and other preparation processes were the same as in Example 1, and the obtained sample was named 20-Vrm-HP5-16B.

[0089] 3. Cellulose hydrolysis

[0090] The catalytic performance test method is as in Example 1. The performance results are as Figure 4 shown.

[0091] Example 10

[0092] 1. Preparation of acid-modified vermiculite

[0093] The acid is changed to 10 wt% phosphoric acid, and other synthesis processes are the same as in Example 2, and the obtained sample is Vrm-HP10.

[0094] 2. Catalyst preparation

[0095] Replace the vermiculite in Step 1 of Example 1 with the acid-modified vermiculite Vrm-HP10, and other preparation processes are the same as in Example 1. The obtained sample is named 20-Vrm-HP10-16B.

[0096] 3. Cellulose hydrolysis

[0097] The catalytic performance test method is as in Example 1. The performance results are as Figure 4 shown.

[0098] Example 11

[0099] 1. Preparation of acid-modified vermiculite

[0100] The acid is changed to 15 wt% phosphoric acid, and other synthesis processes are the same as in Example 2, and the obtained sample is Vrm-HP15.

[0101] 2. Catalyst preparation

[0102] Replace the vermiculite in Step 1 of Example 1 with the acid-modified vermiculite Vrm-HP15, and other preparation processes are the same as in Example 1. The obtained sample is named 20-Vrm-HP15-16B.

[0103] 3. Cellulose hydrolysis

[0104] The catalytic performance test method is as in Example 1. The performance results are as Figure 4 shown.

[0105] Example 12

[0106] 1. Preparation of acid-modified vermiculite

[0107] The acid is changed to 20 wt% phosphoric acid, and other synthesis processes are the same as in Example 2, and the obtained sample is Vrm-HP20.

[0108] 2. Catalyst preparation

[0109] Replace the vermiculite in Step 1 of Example 1 with the acid-modified vermiculite Vrm-HP20, and other preparation processes are the same as in Example 1. The obtained sample is named 20-Vrm-HP20-16B.

[0110] 3. Cellulose hydrolysis

[0111] The catalytic performance test method is as in Example 1. The performance results are as Figure 4 shown.

[0112] Example 13

[0113] 1. Preparation of acid-modified vermiculite

[0114] The acid is changed to 25 wt% phosphoric acid, and other synthesis processes are as in Example 2, and the obtained sample is Vrm-HP25.

[0115] 2. Catalyst preparation

[0116] Replace the vermiculite in Step 1 of Example 1 with the acid-modified vermiculite Vrm-HP25, and other preparation processes are the same as in Example 1, and the obtained sample is named 20-Vrm-HP25-16B.

[0117] 3. Cellulose hydrolysis

[0118] The catalytic performance test method is as in Example 1. The performance results are as Figure 4 shown.

[0119] Example 14

[0120] 1. Preparation of acid-modified vermiculite

[0121] The acid is changed to 30 wt% phosphoric acid, and other synthesis processes are as in Example 2, and the obtained sample is Vrm-HP30.

[0122] 2. Catalyst preparation

[0123] Replace the vermiculite in Step 1 of Example 1 with the acid-modified vermiculite Vrm-HP30, and other preparation processes are the same as in Example 1, and the obtained sample is named 20-Vrm-HP30-16B.

[0124] 3. Cellulose hydrolysis

[0125] The catalytic performance test method is as in Example 1. The performance results are as Figure 4 shown.

[0126] Example 15

[0127] 1. Preparation of acid-modified vermiculite

[0128] The acid is changed to 35 wt% phosphoric acid, and other synthesis processes are as in Example 2, and the obtained sample is Vrm-HP35.

[0129] 2. Catalyst preparation

[0130] Replace the vermiculite in Step 1 of Example 1 with acid-modified vermiculite Vrm-HP35. The other preparation processes are the same as those in Example 1, and the obtained sample is named 20-Vrm-HP35-16B.

[0131] 3. Cellulose hydrolysis

[0132] The catalytic performance test method is the same as that in Example 1. The performance results are as Figure 4 shown.

[0133] Example 16

[0134] Modify vermiculite (Vrm) with cetyltrimethylammonium bromide (CTAB) aqueous solutions at 5 g / L and 10 g / L respectively. The synthesis process is the same as that in Example 1 to obtain catalyst samples 5-Vrm-16B and 10-Vrm-16B.

[0135] The catalytic performance test method is the same as that in Example 1. The TRS yield is as Figure 5 shown.

[0136] Example 17

[0137] Modify acid-modified vermiculite Vrm-HP15 with cetyltrimethylammonium bromide (CTAB) aqueous solutions at 5 g / L and 10 g / L respectively. The synthesis process is the same as that in Example 11 to obtain catalyst samples 5-Vrm-HP15-16B and 10-Vrm-HP15-16B.

[0138] The catalytic performance test method is the same as that in Example 1. The TRS yield is as Figure 5 shown.

[0139] Example 18

[0140] Modify acid-modified vermiculite Vrm-HS15 with cetyltrimethylammonium bromide (CTAB) at 5 g / L and 10 g / L respectively. The synthesis process is the same as that in Example 2 to obtain catalyst samples 5-Vrm-HS15-16B and 10-Vrm-HS15-16B.

[0141] The catalytic performance test method is the same as that in Example 1. The TRS yield is as Figure 5 shown.

[0142] Example 19

[0143] Modify acid-modified vermiculite Vrm-HP35 with cetyltrimethylammonium bromide (CTAB) aqueous solutions at 5 g / L and 10 g / L respectively. The synthesis process is the same as that in Example 15 to obtain catalyst samples 5-Vrm-HP35-16B and 10-Vrm-HP35-16B.

[0144] The catalytic performance test method is the same as that in Example 1. The TRS yield is as Figure 5as shown

[0145] Example 20

[0146] Vermiculite Vrm-HS35 modified with cetyltrimethylammonium bromide (CTAB) aqueous solutions at 5 g / L and 10 g / L respectively was used. The synthesis process was the same as that in Example 3 to obtain catalyst samples 5-Vrm-HS35-16B and 10-Vrm-HS35-16B.

[0147] The catalytic performance test method was as in Example 1. The TRS yield was as Figure 5 shown

[0148] Example 21

[0149] Vermiculite (Vrm) was modified with DMSO aqueous solution at 20 g / L and DTAB aqueous solution at 20 g / L respectively. The synthesis process was the same as that in Example 1 to obtain two catalyst samples.

[0150] The catalytic performance test method was as in Example 1. The TRS yield was as Figure 6 shown

[0151] Example 22

[0152] Vrm-HP15 was modified with DMSO aqueous solution at 20 g / L and DTAB aqueous solution at 20 g / L respectively. The synthesis process was the same as that in Example 11 to obtain two catalyst samples.

[0153] The catalytic performance test method was as in Example 1. The TRS yield was as Figure 6 shown

[0154] Example 23

[0155] Vrm-HS15 was modified with DMSO aqueous solution at 20 g / L and DTAB aqueous solution at 20 g / L respectively. The synthesis process was the same as that in Example 2 to obtain two catalyst samples.

[0156] The catalytic performance test method was as in Example 1. The TRS yield was as Figure 6 shown

[0157] Example 24

[0158] Vrm-HP35 was modified with DMSO aqueous solution at 20 g / L and DTAB aqueous solution at 20 g / L respectively. The synthesis process was the same as that in Example 15 to obtain two catalyst samples.

[0159] The catalytic performance test method was as in Example 1. The TRS yield was as Figure 6 shown

[0160] Example 25

[0161] Vrm-HS35 was modified with 20 g / L DMSO and 20 g / L DTAB aqueous solution respectively. The synthesis process was the same as that in Example 3 to obtain two catalyst samples.

[0162] The catalytic performance test method was as in Example 1. The TRS yield was as Figure 6 shown.

[0163] Example 26

[0164] Vrm was modified with 20 g / L SDS and 20 g / L SLS aqueous solution respectively. The synthesis process was the same as that in Example 1 to obtain two catalyst samples.

[0165] The catalytic performance test method was as in Example 1. The TRS yield was as Figure 7 shown.

[0166] Example 27

[0167] Vrm-HP15 was modified with 20 g / L SDS and 20 g / L SLS aqueous solution respectively. The synthesis process was as in Example 11 to obtain two catalyst samples.

[0168] The catalytic performance test method was as in Example 1. The TRS yield was as Figure 7 shown.

[0169] Example 28

[0170] Vrm-HS15 was modified with 20 g / L SDS and 20 g / L SLS aqueous solution respectively. The synthesis process was as in Example 2 to obtain two catalyst samples.

[0171] The catalytic performance test method was as in Example 1. The TRS yield was as Figure 7 shown.

[0172] Example 29

[0173] Vrm-HP35 was modified with 20 g / L SDS and 20 g / L SLS aqueous solution respectively. The synthesis process was as in Example 15 to obtain two catalyst samples.

[0174] The catalytic performance test method was as in Example 1. The TRS yield was as Figure 7 shown.

[0175] Example 30

[0176] Vrm-HS35 was modified with 20 g / L SDS and 20 g / L SLS aqueous solution respectively. The synthesis process was as in Example 3 to obtain two catalyst samples.

[0177] The catalytic performance test method was as in Example 1. The TRS yield was as Figure 7 shown.

[0178] Comparative Example 1

[0179] Using natural vermiculite as a catalyst, the catalytic performance test method was the same as in Example 1. The TRS yield was 19.5%.

Claims

1. Application of an organically modified vermiculite-based catalyst in the preparation of reducing sugars by cellulose hydrolysis reaction, Characterized in that: The preparation method of the organically modified vermiculite-based catalyst comprises the following steps: Prepare an aqueous surfactant solution with a concentration of 5 - 20 g / L, where the surfactant is selected from cetyltrimethylammonium bromide or dodecyltrimethylammonium bromide. Add acid-modified vermiculite to the aqueous surfactant solution and stir, then ultrasonically disperse it evenly. Then place the mixed solution in a closed container, place it in a constant temperature water bath, and shake it at 50 - 80 °C for 3 - 8 h. After the reaction ends, cool it to room temperature. Centrifuge and wash the post-reaction mixed solution until the pH of the supernatant is 7 - 8. After the washing ends, take out the lower-layer solid, dry it, and grind it into 200 - 300 mesh to obtain the organically modified vermiculite-based catalyst.

2. The application according to claim 1, Characterized in that: The acid-modified vermiculite is prepared by the following method: Add unmodified vermiculite to a 5 - 40 wt% acid solution, ultrasonically disperse it evenly to obtain a mixed solution, stir and react the obtained mixed solution at 60 - 100 °C for 3 - 8 hours. After the reaction ends, cool it to room temperature, centrifuge and wash it until the pH of the supernatant is 6 - 7, and finally dry it to obtain acid-modified vermiculite.

3. The application according to claim 2, Characterized in that: The acid is sulfuric acid, phosphoric acid, nitric acid or hydrochloric acid.

4. The application according to claim 3, Characterized in that: The acid solution is a 15 - 35 wt% sulfuric acid solution or phosphoric acid solution.

5. The application according to claim 1, Characterized in that: The concentration of the aqueous surfactant solution is 20 g / L.

6. The application according to claim 1, Characterized in that: The specific application is as follows: Add cellulose, an organically modified vermiculite-based catalyst and deionized water into a hydrothermal reaction kettle, seal it and heat it to 195 - 215 °C, and carry out a hydrolysis reaction for 2 - 5 hours to generate reducing sugars.

7. The application according to claim 6, Characterized in that: The feeding ratio of the cellulose, the organically modified vermiculite-based catalyst and the deionized water is 1 g : 0.12 - 0.25 g : 10 - 25 mL.